FREQUENCY OF ACUTE KIDNEY INJURY AMONG CHILDREN (AGE LESS THAN 5 YEARS) WITH SEPSIS (The Research of Medical Science Review, 2025)
Background: Acute kidney injury (AKI) is a common and serious complication in children with sepsis, especially in those under the age of 5 years. Sepsis-induced AKI leads to significant morbidity and mortality. Objective: This study aimed to investigate the frequency of AKI among children with sepsis, identify risk factors, and evaluate therapeutic interventions. Methods: This was a prospective cross-sectional study conducted at the Department of Paediatric Medicine, The Children’s Hospital & University of Child Health Sciences, Lahore. The study included 120 children aged 1 month to 5 years, diagnosed with sepsis. AKI was classified using the pediatric RIFLE criteria. Data on demographic details, clinical characteristics, therapeutic interventions, and outcomes were collected. Results: Out of 120 children, 48 (40%) developed AKI. The majority (22 children, 18.3%) had stage 1 AKI, 16 (13.3%) had stage 2, and 10 (8.3%) had stage 3 AKI. Age group 1 month to 1 year showed the highest incidence of AKI (50%). The duration of sepsis was significantly associated with AKI (p = 0.02), with children experiencing prolonged sepsis more likely to develop AKI. Therapeutic interventions such as intravenous fluids were used in 62.5% of AKI cases, and 37.5% required renal replacement therapy. At discharge, 87.5% of AKI patients had recovered without renal impairment, while 12.5% required ongoing dialysis. Conclusions:It is concluded that AKI is prevalent in children with sepsis, particularly in those under 1 year of age. Prolonged sepsis duration was a significant risk factor for the development of AKI. Timely interventions, including fluid resuscitation, are essential for preventing renal damage, but severe cases may require renal replacement therapy.